2023
DOI: 10.1111/ppl.14057
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and exogenous H2O2 improve gas exchange, osmoregulation, and antioxidant metabolism in quinoa under drought stress

Hassan Iqbal,
Chen Yaning,
Muhammad Waqas
et al.

Abstract: Climate change‐induced concurrent drought and salinity stresses significantly threaten global crop yields, yet the physio‐biochemical responses to combined stress in quinoa remain elusive. This study evaluated quinoa responses under four growth conditions: well‐watered, drought stress, salt stress, and drought + salt stress with (15 mM) or without (0 mM) exogenous hydrogen peroxide (H2O2) application. All examined stresses (alone or in combination) reduce quinoa growth and net photosynthesis, although salt str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
(156 reference statements)
1
1
0
Order By: Relevance
“…The effect of drought on quinoa performance depends on the variety and degree of stress and is also influenced by other environmental factors. Results revealed that drought stress reduces quinoa growth and yield in the present study, and these results correspond with previous studies ( Huan et al., 2022 ; Mahdavi Rad et al., 2022 ; Abbas et al., 2023 ; Iqbal et al., 2023 ). However, H 2 O 2 application significantly improved growth attributes, chlorophyll contents, antioxidant enzyme activities, osmolyte accumulation (proline, TSP, and GB), and reduced MDA contents ( Tables 3 , 4 ; Figures 3 , 4 ), ultimately resulting in increased drought tolerance.…”
Section: Discussionsupporting
confidence: 93%
“…The effect of drought on quinoa performance depends on the variety and degree of stress and is also influenced by other environmental factors. Results revealed that drought stress reduces quinoa growth and yield in the present study, and these results correspond with previous studies ( Huan et al., 2022 ; Mahdavi Rad et al., 2022 ; Abbas et al., 2023 ; Iqbal et al., 2023 ). However, H 2 O 2 application significantly improved growth attributes, chlorophyll contents, antioxidant enzyme activities, osmolyte accumulation (proline, TSP, and GB), and reduced MDA contents ( Tables 3 , 4 ; Figures 3 , 4 ), ultimately resulting in increased drought tolerance.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, reports suggest that salt stress may alleviate drought damage in quinoa by facilitating the absorption of inorganic solutes for osmotic regulation. Additionally, exogenous application of H 2 O 2 has been found to enhance quinoa's tolerance to both drought and salt stress (Iqbal et al, 2023). It has also been observed that moderate salt stress can stimulate quinoa growth, although the combined treatment of potassium deficiency and salt stress has been shown to significantly reduce stomatal density, stomatal aperture, and biomass (Waqas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%